Taking children seriously : applications of counselling and therapy in education (London : Cassell, 1999)
This book is divided into four parts: Taking issues seriously; Taking practice seriously; Taking Groups seriously; and Taking Schools seriously.
Keywords: Education; Teachers; Educational counseling; Teacher participation in educational counseling